Quality Indicators of Agaricus bisporus after Ultraviolet Treatment - Vladimir V. Kondratenko; Natalia E. Posokina; Natalia I. Fedyanina; Olga V. Karastoyanova; Nadezhda V. Korovkina (Техника и технология пищевых производств)
Ultraviolet treatment increases the shelf life of plant products. It inhibits the changes in the quality indicators of raw materials that are responsible for storage capacity. The research objective was to establish qualitative indicators for champignons (Agaricus bisporus) after ultraviolet treatment. Fresh champignons were placed in plastic trays and sealed in plastic bags. The samples were treated with ultraviolet radiation in ranges A, B, and C. After that, they were stored in a refrigerator at 4 ± 2°C for 16 days, i.e., until the end of storage period. The quality indicators underwent a paired two-sample test, which defined the equality/inequality of variances in replicates and equality/inequality of means at a given error probability (α). The obtained indicators characterized the degradation of mushroom plant tissue after ultraviolet treatment during storage: texture, moisture content, weight loss, soluble solids, pH, lightness, and color. The authors developed a new approach to determine significant changes in the quality indicators and estimated probability values. For each range, they established the most effective dose at α = 0.05 and 0.1. All the indicators proved significant for range A samples at 327.8–800.0 J/m2 and α = 0.05; all indicators were significant except weight loss in the range from 219.5 to 800.0 J/m2 at α = 0.1. For range B samples, pH, color, and lightness were significant at 104.6–200.0 J/m2 and α = 0.05; all but mass loss and texture were significant at 172.2–200.0 J/m2 and α = 0.1. For range C samples, pH, color, and lightness were significant at 412.4–439.5 J/m2 and 755.9–800.0 J/m2 at α = 0.05; all indicators were significant at 363.3–486.2 J/m2 and 728.2–800.0 J/m2 at α = 0.1. The new analytical method made it possible to determine the ranges of external effect intensity, in which the changes in the indicator were significant or insignificant.